Human amniotic membrane as a homograft material in myringoplasty - Harvinder Singh, Dalip Singh (2001)
To evaluate the efficacy of preserved human amniotic membrane as an alternative graft material in terms of its anatomical and functional outcomes in closing tympanic membrane defects during myringoplasties. We also compared it with the standard temporal fascia graft. A prospective review of 50 cases operated for tympanic membrane defects in Hospital University Sains Malaysia from June 1999 to June 2001. Twenty cases used preserved human amniotic membrane and 30 cases used temporal fascia graft. Clinical and audiometric assessment were done 3 months postoperatively. During a period 2 years, a total of 50 ears with tympanic membrane perforations were operated, out of this 28 were males and the remaining 22 were females. The age range was between 10 to 70 years with a mean age of 32.08 years. The operations were carried out by senior surgeons in the department. The surgical approach was either permeatal, endaural or postaural but the technique was limited to underlay or pop in through perforation. Postoperative results were evaluated with respect to the anatomical and functional outcomes. To assess anatomic results, we took into account successful closures, presence of residual perforations, infections, graft dislodgment and lateralization. In the temporal fascia group, successful closure were achieved in 17 (56.7o/o) of 30 cases. Among the 13 failures (43.3%), 6 were due to residual perforation, 4 infections, 2 graft dislodgment and one lateralization. In the human amniotic membrane group, successful closure were achieved in 13 (65%) of 20 cases. Among the 7 failures (35o/o), 4 were residual perforations, 2 due to infection and one graft lateralization. In the evaluation of the functional outcomes, both groups showed significant difference between pre and postoperative mean air conduction thresholds component of hearing. However, a significant closure of air-bone gap was only observed in the human amniotic membrane group. Human amniotic membrane is a simple, safe and cost effective technique for repairing perforated tympanic membranes. It gives good anatomic and functional results and is comparable to the standard temporal fascia graft material so widely used today.